2020
DOI: 10.1055/s-0040-1708521
|View full text |Cite
|
Sign up to set email alerts
|

HLA Polymorphisms and Food Allergy Predisposition

Abstract: Food allergy (FA) is a growing health problem that affects ∼8% of the children worldwide. Although the prevalence of FA is increasing, the underlying genetic mechanisms responsible for the onset of this immune disorder are not yet clarified. Genetic factors seem to play a leading role in the development of FA, though interaction with environmental factors cannot be excluded. The broader network of genetic loci mediating the risk of this complex disorder remains to be identified. The human leucocyte antigen (HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…HLA‐DRB1 and HLA‐DQB1 (encoding for the β‐chains) belong to MHC class II, are closely linked within the genetic loci, share common regulatory features in their promoter regions 25 and common CpG islands within exon 2 18 . Also, genetic variants within HLA‐DQB1 and HLA‐DRB1 sequences have strongly been associated with predisposition to FA, 15,16 but the linkage between DNA methylation and SNPs across these loci has not yet been elucidated. CpG73 and CpG41 also include DNAse hypersensitive sites, indicating essential trans‐acting factor occupancy.…”
Section: Resultsmentioning
confidence: 99%
“…HLA‐DRB1 and HLA‐DQB1 (encoding for the β‐chains) belong to MHC class II, are closely linked within the genetic loci, share common regulatory features in their promoter regions 25 and common CpG islands within exon 2 18 . Also, genetic variants within HLA‐DQB1 and HLA‐DRB1 sequences have strongly been associated with predisposition to FA, 15,16 but the linkage between DNA methylation and SNPs across these loci has not yet been elucidated. CpG73 and CpG41 also include DNAse hypersensitive sites, indicating essential trans‐acting factor occupancy.…”
Section: Resultsmentioning
confidence: 99%
“…Associations between CR sensitization and HLA class II antigens have been suggested 56,57 and consistently shown in food allergies. 58,59 In addition, we measured basal levels of non-antigen specific regulatory T cells and observed that T cells inversely correlated with the effector CD4+ T cell responses although it did not reach statistical significance. These results were not unexpected and were consistent with previous observations from Bacher et al 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Associations between CR sensitization and HLA class II antigens have been suggested 56 , 57 and consistently shown in food allergies. 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…HLA-DRB1 and HLA-DQB1 (encoding for the β-chains) belong to MHC class II, are closely linked within the genetic loci, share common regulatory features in their promoter regions 23 and common CpG islands within exon 2 18 . Also, genetic variants within HLA-DQB1 and HLA-DRB1 sequences have strongly been associated with predisposition to FA 15,16 , but the linkage between DNA methylation and single-nucleotide polymorphisms (SNPs) across these loci has not yet been elucidated. CpG73 and CpG41 also include DNAse hypersensitive sites, indicating essential trans-acting factor occupancy.…”
Section: Methylation Status Of Hla-drb1 Cpg41 and Co-existence Of Gen...mentioning
confidence: 99%
“…Cell-processed antigens' presentation by MHC class II to CD4 + T lymphocytes, stimulates the antigen-specific hypersensitivity type I allergic reaction. GWAS studies and review analysis have provided convincing evidence that HLA-DRand HLA-DQ genes' polymorphic regions harbor significant genetic and epigenetic risk for FA 15,16 .…”
Section: Introductionmentioning
confidence: 99%